ANALISIS KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN: PERBANDINGAN PADA MODERN RETAIL MINIMARKET DENGAN TOKO KELONTONG DI KOTA SURABAYA - jurnalpps pps; Hendrik Rizqiawan; Dwi Prihantono (Jurnal Manajerial Bisnis, 2020)
This research aims to explain the analysis of service quality to customer satisfaction, also to know there is a difference between service quality analysis to customer satisfaction, at modern retail minimarket and grocery store in city Surabaya. Respondents in this study as much as 100 people who are at least 16 years old, ever shop in modern retail minimarket and grocery store, and stay settled or while in the city of Surabaya. Based on the results of the analysis, it is known that there is a significant influence between quality of service to customer satisfaction in modern retail minimarket and grocery store in Surabaya city. And it is also known that there is a difference between service quality analysis on customer satisfaction in modern retail minimarket and grocery store based on different test, where both of these variables have GIS. (2-tailed) = 0.000 means below 0.05.Keywords: modern retail minimarket, grocery store, service qualiy, customer satisfaction